Patterns of Integration of Higher Education Curriculum with Industry Through the Development of Arts Education Residency Center - Iriaji, Iriaji; Prasetyo, Abdul Rahman; Rahayu, Wening Patmi; Roziqin, Mohamad Firzon Ainur; Surya, Eka Putri; Wijaya, Ginanjar Atma; Marcelliantika, Adinda; Aruna, Alby (Civiliza Publishing, 2024)
This community service program aims to develop a model for integrating university curricula with industry through the establishment of an Art Education Residency Center. The methodology includes industry needs analysis, program design, and program implementation evaluation. The Residency Center is designed to provide students with opportunities to interact directly with art industry practitioners, thereby integrating academic theory with practical experience. The results of this program indicate significant improvements in students' practical skills, expansion of professional networks, and readiness to face industry challenges. Evaluations through surveys and in-depth interviews confirm the program's effectiveness in bridging the gap between education and industry. This program makes a significant contribution to modernizing art education curricula, ensuring their relevance to current and future industry needs.